Vocational education and training and youth employment - some experiences from Germany - Münchhausen, Gesa [Verfasser] (My University, 2014)
"This paper gives an overview of the vocational education and training system and the youth employment in Germany and the linkage between learning and requirements of the labor market. This paper shows several of the relevant elements and also developments of the German VET system." (Authors' abstract, BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; G 1.2.2.4 Arbeitslosigkeit; P 1.1 Jugendliche; Berufsbildungssystem; Berufsbildungspolitik; Jugendarbeitslosigkeit; Beziehung Bildungssystem Beschäftigungssystem